2021
DOI: 10.1080/19415257.2021.1879215
|View full text |Cite
|
Sign up to set email alerts
|

Virtual team professional learning and development for practitioners in education

Abstract: Surprisingly little has been written about the notion of virtual teams in schooling contexts and less on the role of virtual teams in the professional learning and development (PLD) of teachers. Virtual teams are groups that use technologies to collaborate to address common goals. Members may work at in different locations, in different organisations, or at different times so that the electronic communication media becomes an important feature in the feasibility of the work. Increasingly, technologies are used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 43 publications
1
20
0
2
Order By: Relevance
“…Alongside declaring their preferences towards the format of lifestyle sport CPD, participants also identified the major factors currently restricting their engagement with such provision. Consistent with existing research (see Charteris et al [87]), logistical issues such as time and funding were cited as barriers preventing engagement with lifestyle sport CPD. Moreover, the participants indicated that they lacked an awareness of how to source and access lifestyle sport CPD, which significantly hindered their attendance [55].…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Alongside declaring their preferences towards the format of lifestyle sport CPD, participants also identified the major factors currently restricting their engagement with such provision. Consistent with existing research (see Charteris et al [87]), logistical issues such as time and funding were cited as barriers preventing engagement with lifestyle sport CPD. Moreover, the participants indicated that they lacked an awareness of how to source and access lifestyle sport CPD, which significantly hindered their attendance [55].…”
Section: Discussionsupporting
confidence: 64%
“…In addressing this area, the findings from this research indicate that the participants prefer the use of online CPD and social media to access lifestyle sport content. While there are challenges associated with online CPD (e.g., practical relevance, reduced social interaction), the participants believed this approach would allow them to save time and travel in comparison to face-to-face alternatives [87], while helping to "fill specific gaps in teacher education and knowledge" [47] (p. 11). Recent research has argued that online CPD formats (e.g., webinars, podcasts, online workshops, virtual conferences) are transforming the landscape of PE teacher learning by reducing isolation and enabling customised approaches which impacts upon practice [47,86,88].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent article by Charteris et al (2021) discussed the shift K12 teachers experienced from in-person to virtual teams due to the COVID-19 pandemic. Drawing on a professional learning and development (PLD) framework from the Australian Institute for Teaching and School Leadership (AITSL, 2012), Charteris et al (2021) discuss how practitioners in education can use virtual teams to deliver PLD that is relevant, collaborative, and futurefocused. Since literature is almost absent on virtual teams for K12 teachers, Charteris et al (2021) call for more research and models for virtual team application in education to support teacher PLD.…”
Section: Introductionmentioning
confidence: 99%
“…Drawing on a professional learning and development (PLD) framework from the Australian Institute for Teaching and School Leadership (AITSL, 2012), Charteris et al (2021) discuss how practitioners in education can use virtual teams to deliver PLD that is relevant, collaborative, and futurefocused. Since literature is almost absent on virtual teams for K12 teachers, Charteris et al (2021) call for more research and models for virtual team application in education to support teacher PLD. Overall, Charteris et al (2021) found that teachers successfully transitioned into virtual teams during the pandemic and need continued PLD that supports their contexts.…”
Section: Introductionmentioning
confidence: 99%